2016
DOI: 10.1007/s00392-016-0987-8
|View full text |Cite
|
Sign up to set email alerts
|

Bonus-freeze: benefit or risk? Two-year outcome and procedural comparison of a “bonus-freeze” and “no bonus-freeze” protocol using the second-generation cryoballoon for pulmonary vein isolation

Abstract: BackgroundSecond-generation cryoballoon based pulmonary vein isolation has demonstrated encouraging acute and mid-term clinical outcome. Customarily, a bonus-freeze is applied after successful pulmonary vein isolation.ObjectiveTo compare the long-term clinical outcome and safety profile of a bonus-freeze and a no bonus-freeze protocol.MethodsA total of 120 consecutive patients with paroxysmal [95/120 (79 %)] or persistent atrial fibrillation [25/120 (21 %)] underwent CB2-based PVI. Freeze-cycle duration was 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 22 publications
2
58
0
Order By: Relevance
“…Five observational studies provided data on the short‐ to midterm outcome in patients after PVI using CB‐Adv for the treatment of persistent AF, being in line with published data after RF ablation . Interest in using CB‐Adv for PVI is increasing, because procedure times are shorter with CB ablation than with RF ablation, due to reduced freeze cycle times and single‐shot applications, not being associated with smaller lesion surface areas using nitrous oxide as refrigerant …”
Section: Discussionsupporting
confidence: 54%
“…Five observational studies provided data on the short‐ to midterm outcome in patients after PVI using CB‐Adv for the treatment of persistent AF, being in line with published data after RF ablation . Interest in using CB‐Adv for PVI is increasing, because procedure times are shorter with CB ablation than with RF ablation, due to reduced freeze cycle times and single‐shot applications, not being associated with smaller lesion surface areas using nitrous oxide as refrigerant …”
Section: Discussionsupporting
confidence: 54%
“…Although the CB1 had several limitations, clinical results when using the further generation CBs have been shown to be comparable to RF . The initially most commonly applied ablation protocol has been the bonus‐freeze protocol characterized by an additional empiric freeze cycle following documentation of electrical PVI . Although the current trend is to perform CB ablations without an additional bonus freeze, the optimal dosing strategy in terms of duration of cryoapplication per freeze is not yet established.…”
Section: Discussionmentioning
confidence: 99%
“…These observations provide further justification to pursue double freeze‐thaw cycles at successful sites pending more definitive evidence . There are, however, some data to suggest that a single freeze‐thaw cycle is sufficient for the current generation cryoballoon, which creates extensive encircling lesions to electrically isolate pulmonary veins . Double freeze‐thaw cycles remain the norm for cryoablation of other tissues including skin, liver, and prostate …”
Section: Discussionmentioning
confidence: 99%
“…10,11 There are, however, some data to suggest that a single freeze-thaw cycle is sufficient for the current generation cryoballoon, which creates extensive encircling lesions to electrically isolate pulmonary veins. 9,12 Double freeze-thaw cycles remain the norm for cryoablation of other tissues including skin, liver, and prostate. 13,14 We previously reported that the incidence of thrombus formation is far lower with cryoablation when compared to radiofrequency energy.…”
Section: Discussionmentioning
confidence: 99%